Comparison of two DNA extraction protocols from leave samples of Cotinus coggygria, Citrus sinensis and Genus juglans - Fallah, F.; Minaei Chenar, H.; Amiri, H.; Omodipour, S.; Shirbande Ghods, F.; Kahrizi, D.; Sohrabi, M.; Ghorbani, T.; Kazemi, E. (Cellular and Molecular Biology, 2017)
High quality DNA is essential for molecular research. Secondary metabolites can affect the quantity and quality DNA. In current research two DNA isolation methods including CTAB and Delaporta (protocols 1 & 2 respectively) were applied in three leave samples from Cotinus coggygria, Citrus sinensis and Genus juglans that their leaves are rich of secondary metabolites. We successfully isolated DNA from C. coggygria, C. sinensis and Genus Juglans using the two protocols described above. Good quality DNA was isolated from C. coggygria, C. sinensis and Genus Juglans using protocol 1, while protocol 2 failed to produce usable DNA from these sources. The highest amount of DNA (1.3-1.6) was obtained from them using protocol 1. As we discovered, procedure 1 may work better for plants with secondary metabolites.